2017
DOI: 10.1186/s13256-017-1319-y
|View full text |Cite
|
Sign up to set email alerts
|

Port site recurrence after laparoscopic radical nephrectomy: a case report

Abstract: BackgroundDue to the recent development of laparoscopic devices, laparoscopic radical nephrectomy is the standard procedure for localized renal cell carcinoma. However, some studies have reported postoperative port site metastasis in several cancers.Case presentationA 68-year-old Asian-Japanese man was referred to our hospital for a further examination of his right renal tumor in 2009. Due to a clinical suspicion of renal cell carcinoma, laparoscopic nephrectomy was performed. The histopathological diagnosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…In comparison, the risk of PSM might have been lower in the present case. However, Shimokihara et al [10] reported a case of PSM with an initially low-risk RCC similar to the present case. Therefore, we suggest that any tumor suspicious for PSM should be resected.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…In comparison, the risk of PSM might have been lower in the present case. However, Shimokihara et al [10] reported a case of PSM with an initially low-risk RCC similar to the present case. Therefore, we suggest that any tumor suspicious for PSM should be resected.…”
supporting
confidence: 83%
“…The preoperative differentiation between IPT and PSM of RCC is difficult because of the rarity of both conditions, which were reported in very few case reports [2][3][4][9][10][11]. Based on the limited information, both IPT and PSM of RCC are usually asymptomatic while retaining a small tumor burden.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 This report and a simultaneous study using a national database, 10 has led to modification of national guidelines to caution against MIS for cervical cancer and to cessation of MIS cervical cancer surgery at some institutions. 14 Oncologic concerns for one type of cancer may not translate across all types, however, among patients with kidney cancer, there are published reports of atypical recurrences following MIS [15][16][17] and we have noticed these in our practice as well. Thus, there is a need to better understand this scope of this issue across a broader population.…”
Section: Introductionmentioning
confidence: 77%
“…Nguyen et al verglichen die Rezidivraten des Harnblasenkarzinoms nach offenen und roboterassistierten radikalen Zystektomien, wobei eine höhere Inzidenz einer Peritonealkarzinose bei roboterassistierten Zystektomien (21 %) im Vergleich zu offenen Zystektomien (8 %) beschrieben wurde 9 . Bezüglich des Nierenzellkarzinoms sind nach laparoskopische Tumornephrektomie 17 Fälle mit Port-site Metastasen in der Literatur beschrieben 10 11 .…”
Section: Diskussionunclassified